PARTISIPASI MASYARAKAT DAN MUTU PENDIDIKAN DI KABUPATEN BOJONEGORO - Minarti, Sri (At-Tuhfah : Jurnal Studi Keislaman, 2019)
“The quality of education is the top priority of every education unit in Bojonegoro Regency so that various activities programs are raised by schools and establish cooperation with communities especially parents of student guardians or committees in the form of active participation and involvement in various fields. This study included the qualitative type of data collection with observation, documents, and authority, analyzed by qualitative descriptive to answer the research focus on the form of committee participation and the quality of education in SMP N 1 and SMP N 2 Bojonegoro. The results of the study indicate that committee participation in educational units in the academic and non-academic fields, for example, input curriculum development, infrastructure or funding. The quality of education in two schools can be proven by the fulfillment of eight educational standards and added one character standard which is input from the committee as well as high public interest in the school, and alumni accepted in favorite secondary schools (input, process, and output). The answer to the two research focuses is in accordance with Johnlitlle's theory of participation and Deming's theory of quality.”